Qur’anic words: An analysis on Shihab’s rules of exegesis in Tafsir Al-Mishbah - Sakat A.A.; Usman A.H.; Masruri M.; Amin M.F.M.; Ahmad M.N.; Kadir M.N.A. (Mediterranean Center of Social and Educational Research, 2024)
Indexed by Scopus